Mutational analysis of simian virus 40 T antigen: isolation and characterization of mutants with deletions in the T-antigen gene. - Pipas, J M (1983)
A series of mutants of simian virus 40 has been constructed with deletions in the coding sequence for large T antigen. Nucleotide sequence analysis indicates that 4 mutants have in-phase and 11 have out-of-phase deletions. Mutant DNAs were assayed for the following activities: the ability to form plaques, the ability to produce T antigen as scored by indirect immunofluorescence, viral DNA replication, and morphological transformation of rat cells. Two viable mutants were found, and these had deletions confined to the carboxyl terminus of T antigen. Only those mutants coding for polypeptides greater than 40% of the length of wildtype T antigen produced detectable nuclear fluorescence. The two viable mutants with deletions in the carboxyl terminus of the protein retained the ability both to replicate their DNA, although at a reduced level, and to transform nonpermissive cells. Mutants with sequence changes that result in the loss of more than 117 amino acids from the carboxyl terminus were not viable and were also defective in the DNA replication and transformation functions of T antigen, although several produced detectable nuclear fluorescence. These functions were also sensitive to the removal of amino acids near the amino terminus and in the middle of the protein.